Influence of Different Ceramics on Resin Cement Knoop Hardness Number - Borges, G. A.; Agarwal, P.; Miranzi, B. A. S.; Platt, J. A.; Valentino, T. A.; Santos, Paulo Henrique dos [UNESP] (Operative Dentistry Inc, 2008)
This study evaluated: 1) the effect of different ceramics on light attenuation that could affect microhardness, measured as the Knoop Hardness Number (KHN), of a resin cement immediately and 24 hours after polymerization and 2) the effect of different activation modes (direct light-activation, light activation through ceramics and chemical activation) on the KHN of a resin cement.Resin cement Rely X ARC (3M ESPE) specimens 5.0 mm in diameter and 1.0 nun thick were made in a Teflon mold covered with a polyester film. The cement was directly light activated for 40 seconds with an XL 2500 curing unit (3M ESPE) with 650 mW/cm(2), light activated through ceramic discs of Duceram Plus (DeguDent), Cergogold (DeguDent), IPS Empress (Ivoclar), IPS Empress 2 (Ivoclar), Procera. (NobelBiocare), In Ceram Alumina (Vita) and Cercon (DeguDent), having a 1.2 mm thickness or chemically activated without light application. The resin cement specimens were flattened, and KHN was obtained using an HMV 2 microhardness tester (Shimadzu) with a load of 50 g applied for 15 seconds 100 pin from the irradiated surface immediately and after storage at 37 degrees C for 24 hours. Ten measurements were made for each specimen, with three specimens for each group at each time. The data were submitted to ANOVA and Tukey's test (p=0.05). The KHN of the resin cement was not only affected by the mode of activation, but also by the post-activation testing time. The mean KHN of the resin cement for chemical activation and through all ceramics showed statistically significant lower values compared to direct activation immediately and at 24 hours. The KHN for 24 hours post-activation was always superior to the immediate post-activation test except with direct activation. The most opaque ceramics resulted in the lowest KHN values.